The Prevalance Overview of ARI Sufferers in the Mining Environment at Cinta Jaya Inc, Molawe District - Adryana , Vita; Azizi Jayadipraja , Erwin; Sriningsih , Chun; Suatia , Waode (Waluya The International Science of Health Journal, 2022)
20 Introduction: Mining activities also cause traffic disturbances due to the back and forth of operational vehicles and transporters going and out of the special terminal area,causing a decrease in air quality and noise which can increase the prevalence of Ari based on data from molawe health center with a population 0f 5291,30 ARI patient, cases in 2019 and there were 37 cases in 2020 and 42 casess in 2021 this can 2021.this affect the health status of the community in the mining envirotment of the molawe sub-district Method: The method used in this study is descriptive research method. The descriptive method was chosen because the study carried out aims to describe the data naturally. The data used are secondary data and documents from the Health Office of Southeast Sulawesi Province, Limbo Health Center, Molawe District, 2019 - 20121. North Konawe Regency, Southeast Sulawesi Province. Result: It was concluded that there was a relationship between age and gender with the incidence of ARI in infants Smoking Habits From 42 respondents, the results showed that most of the respondents were exposed to cigarette smoke, namely 34 respondents or 81.0% and the remaining only 8 respondents (19%) who had no exposure to cigarette smoke. Based on these data, it can be concluded that most children under five are exposed to cigarette smoke. Conclusion: The factors that influence the increasing prevalence of ARI are redidental density,smoking/behavior and mining activities that are very at risk for suffering from ARI disease